Komparasi antara Logika Aristotelian dan Logika Modern dalam prespektif pendidikan islam (Pusat Riset dan Inovasi Nasional, 2026)
This research examines the comparison between Aristotelian Logic and Modern Logic from the perspective of Islamic education. It aims to understand their concepts, significant differences, the perspective of Islamic education, and their contribution to critical thinking. The study employs a philosophical-comparative approach. The findings indicate that Aristotelian Logic, with its deductive approach and syllogism, emphasizes universal truth and coherence. In contrast, Modern Logic focuses on symbolic formalism and empirical verification. Islamic education views logic as an epistemological tool to harmonize reason (`aql) and revelation (naql). The analysis reveals that integrating both logical systems is not only possible but also strategic. Their synthesis gives rise to